Enhancing collaboration and communication skills through discovery learning in Indonesian language classrooms - Muhammad Yani (Science Center Group, 2025)
Background: Twenty-first century education emphasizes the development of collaboration and communication skills as essential competencies for meaningful learning. Indonesian language classrooms require instructional approaches that promote active engagement, cooperative interaction, and structured discourse construction. Discovery learning has been widely implemented to enhance higher-order thinking; however, empirical evidence regarding its integrated impact on collaboration and communication skills in language education remains limited. Objective: This study aimed to examine the effectiveness of discovery learning in enhancing students’ collaboration and communication skills in Indonesian language classrooms at the secondary school level. Methods: A quasi-experimental design with a pretest–posttest control group approach was employed. Seventy-two Grade VIII students were divided into an experimental group receiving six weeks of discovery learning instruction and a control group receiving conventional instruction. Data were collected using validated collaboration and communication skill rubrics. Descriptive statistics, paired sample t-tests, independent sample t-tests, and effect size analysis were conducted to determine within-group and between-group differences. Results: The findings revealed no significant difference between groups at baseline. After the intervention, the experimental group demonstrated significantly higher scores in both collaboration and communication skills compared to the control group (p < 0.001). Within-group analysis showed substantial improvement in the experimental group, while changes in the control group were not statistically significant. Effect size calculations indicated a strong pedagogical impact of discovery learning on both skill domains. Conclusion: Discovery learning effectively enhances students’ collaboration and communication skills in Indonesian language classrooms. The structured phases of exploration, discussion, verification, and reflection provide a meaningful framework for fostering cooperative engagement and expressive competence. The integration of discovery learning offers a promising instructional strategy for strengthening 21st-century competencies in language education.